Keluhan Muskuloskeletal Pada Sales Promotion Girl (SPG) Mall Pemakai Sepatu Tumit Tinggi Di Kota Denpasar Tahun 2012 - Dewi, Ni Kadek Novita (Community Health)
Sales promotion girl (SPG) have to work wearing high heels for up to 5 hours daily. The used of high heels increased tension in the muscle and most common created musculoskeletal disorders in the foot, knee and spine. This research aims to determine musculoskeletal disorders of SPG who use high heels in Denpasar at 2012. The research was held in four malls in Denpasar. This research is a descriptive quantitative study with cross sectional approach. Sampel taken by proportioned stratified sampling and then selected purposively. Data were collected by interviews using a nordic body map questionnaire and observation by measuring the weight, height, hight of heel, and calculate the body mass index (BMI). Data was carried out through description analysis. The results showed that 96.74% of respondents have musculoskeletal disorders that consist of 88.76% low and 11.24% high musculoskeletal disorder. Most of musculoskeletal disorder occur at foot, calf, waist and back. There was a tendency that musculoskeletal disorder has the same equal with the age, duration of wearing high heels, and heigh of heels increasing. Based on BMI, SPG with normal BMI has lower musculoskeletal disorder than thin and excessive BMI. Thereby SPG should not wear high heels more than 5 cm height and considering the age, BMI and duration of wearing high heel before decided to wear high heel.